Clinical course following diabetic ocular palsy. Issue 638 (December 1978) - Leslie, D.; Ellis, C.
Abstract : Eleven patients who had a diabetic ocular palsy were reviewed. Clinical evidence of microangiopathy or atherosclerosis was infrequent, thus such a palsy does not presage subsequent diabetic complications nor do these observations support the suggestion that diabetic ocular palsies are caused by vascular disease.